Hinfp is a guardian of the somatic genome by repressing transposable elements. - Nirala, N.K.; Li, Q.; Ghule, P.N.; Chen, H.J.; Li, R.; Zhu, L.J.; Wang, R.; Rice, N.P.; Mao, J.; Stein, J.L.; Stein, G.S.; van Wijnen, A.J.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Germ cells possess the Piwi-interacting RNA pathway to repress transposable elements and maintain genome stability across generations. Transposable element mobilization in somatic cells does not affect future generations, but nonetheless can lead to pathological outcomes in host tissues. We show here that loss of function of the conserved zinc-finger transcription factor Hinfp causes dysregulation of many host genes and derepression of most transposable elements. There is also substantial DNA damage in somatic tissues of Drosophila after loss of Hinfp. Interference of transposable element mobilization by reverse-transcriptase inhibitors can suppress some of the DNA damage phenotypes. The key cell-autonomous target of Hinfp in this process is Histone1, which encodes linker histones essential for higher-order chromatin assembly. Transgenic expression of Hinfp or Histone1, but not Histone4 of core nucleosome, is sufficient to rescue the defects in repressing transposable elements and host genes. Loss of Hinfp enhances Ras-induced tissue growth and aging-related phenotypes. Therefore, Hinfp is a physiological regulator of Histone1-dependent silencing of most transposable elements, as well as many host genes, and serves as a venue for studying genome instability, cancer progression, neurodegeneration, and aging.